2006
DOI: 10.1021/jf0606712
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Color Break in Citrus Fruits. Changes in Pigment Profiling and Gene Expression Induced by Gibberellins and Nitrate, Two Ripening Retardants

Abstract: Citrus clementina fruits were repeatedly treated on-tree from mature green until breaker stages with either nitrate or gibberellin, two retardants of external ripening. The natural color break was characterized by a reduction in chlorophyll concentration, a decrease in beta,epsilon-carotenoids, beta-carotene, neoxanthin, and all-E-violaxanthin, and an increase in beta,beta-xanthophylls [mainly (9Z)-violaxanthin and beta-cryptoxanthin]. The two retardants delayed both chlorophyll depletion and total carotenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 29 publications
(47 reference statements)
8
96
0
8
Order By: Relevance
“…In this work it is proposed that sugar regulation may operate via ethylene, whereas GA functions as a repressor of the ethylene-sucrose stimulation. Therefore, GAs as well as nitrates are color break retardants since both delay the chloro-to chromoplast transition (Alós et al, 2006) in contrastethylene (Rodrigo and Zacarías, 2007).…”
Section: External Ripeningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work it is proposed that sugar regulation may operate via ethylene, whereas GA functions as a repressor of the ethylene-sucrose stimulation. Therefore, GAs as well as nitrates are color break retardants since both delay the chloro-to chromoplast transition (Alós et al, 2006) in contrastethylene (Rodrigo and Zacarías, 2007).…”
Section: External Ripeningmentioning
confidence: 99%
“…For example, it has been shown that chlorophyllase, a constitutively expressed gene, does not increase during natural fruit development (JacobWilk et al, 1999). In addition, the expression patterns of carotenoid biosynthetic genes and an associated abundance of carotenoids during ripening have recently been reported (Kato et al, 2004;Rodrigo et al, 2004;Alós et al, 2006). It is noteworthy that citrus peel contains the greatest diversity of carotenoids of any fruit studied to date and their specific accumulation patterns are responsible for the broad range of colors exhibited by PHYSIOLOGY OF CITRUS FRUITING citrus fruits (Gross, 1987).…”
Section: External Ripeningmentioning
confidence: 99%
“…Huff (1984), propone que el nitrógeno tiene un papel protector estabilizando los cloroplastos, pero que no promueve su formación. Considerando los antecedentes y nuestros resultados, proponemos que el nitrógeno, a pesar de ser un metabolito importante modulando la toma de color de los frutos cítricos (Jones y Embleton, 1959;Huff, 1983;Lee y Chapman, 1988;Quiñones et al, 2004;Alós et al 2006), no es un factor desencadenante del proceso.…”
Section: Discussionunclassified
“…Por otro lado, los frutos con el pedúnculo anillado permanecieron más verdes y presentaron mayores niveles de ABA en el flavedo que los control, al igual que la corteza del pedúnculo de la zona conectada al fruto (zona apical). La mayor concentración de N encontrada en los frutos anillados parece no haber afectado la ruta de biosíntesis de ABA, propuesta por Alós et al (2006), frente al agregado exógeno de nitratos.…”
Section: Discussionunclassified
See 1 more Smart Citation